2015
DOI: 10.1016/j.smrv.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of group cognitive behavioral therapy for insomnia

Abstract: SummaryInsomnia is the most common sleep disorder among the general population. Although cognitive behavioral therapy for insomnia (CBT-I) is the psychological treatment of choice, the availability of individual therapy is often not sufficient to meet the demand for treatment. Group treatment can increase the efficiency of delivery, but its efficacy has not been well-established. Randomized controlled trials (RCTs) comparing group CBT-I to a control group in patients with insomnia were identified. A review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
168
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(211 citation statements)
references
References 39 publications
22
168
3
8
Order By: Relevance
“…For example, participants selected for the interventions were characterized by longer SOL, but not lower TST, compared with those not selected for the interventions. These results are also consistent with emerging empirical evidence showing that children and adolescents with anxious and depressive symptoms have particular difficulties with wakefulness in bed (Lovato & Gradisar, 2014), especially sleep initiation (Alfano et al, 2013;Forbes et al, 2008), and with the results of other sleep interventions that have found SOL among the most improved variables (Bei et al, 2013;Bootzin & Stevens, 2005;Clarke et al, 2015;de Bruin et al, 2015de Bruin et al, , 2014Garland et al, 2014;Gradisar, Dohnt, et al, 2011;Gross et al, 2011;Koffel et al, 2015;Schlarb et al, 2011;Trauer et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, participants selected for the interventions were characterized by longer SOL, but not lower TST, compared with those not selected for the interventions. These results are also consistent with emerging empirical evidence showing that children and adolescents with anxious and depressive symptoms have particular difficulties with wakefulness in bed (Lovato & Gradisar, 2014), especially sleep initiation (Alfano et al, 2013;Forbes et al, 2008), and with the results of other sleep interventions that have found SOL among the most improved variables (Bei et al, 2013;Bootzin & Stevens, 2005;Clarke et al, 2015;de Bruin et al, 2015de Bruin et al, , 2014Garland et al, 2014;Gradisar, Dohnt, et al, 2011;Gross et al, 2011;Koffel et al, 2015;Schlarb et al, 2011;Trauer et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…RCT's of pure CBT-I among adolescents (de Bruin et al, 2015;Gradisar, Dohnt, et al, 2011) and adults (for reviews, see Koffel et al, 2015;Trauer et al, 2015) have found medium-large effects favoring the treatment condition for wakefulness in bed variables (sleep onset latency, sleep efficiency, and wake after sleep onset), whereas the current study only demonstrated small-moderate effects for sleep onset latency. However, previous studies have used wait-list comparators (de Bruin et al, 2015;Gradisar, Dohnt, et al, 2011;30% to 40% of studies reviewed by Koffel et al, 2015 andTrauer et al, 2015), clinical samples (de Bruin et al, 2015;Koffel et al, 2015;Trauer et al, 2015), and/or subjective measures of sleep Koffel et al, 2015;Trauer et al, 2015), whereas the current study used an active control comparator, community sample, and subjective and objec- This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Delivering CBT for depression in a group format is a cost-effective alternative to individual treatment [27,28], bipolar disorder [29,30], obsessive compulsive disorder [31], panic disorder [32], panic disorder with agoraphobia [33], insomnia disorder [34,35], sexual abuse in girls [36] and post-traumatic stress disorder [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Chiefly, the widespread dissemination and implementation of CBT-I has been hampered by a lack of qualified providers. Whilst there have been advances in this arena in terms of establishing national training programmes (10) and broadening the range of delivery modalities to engage more efficiently and widely-through creating briefer and more targeted hybrid versions (11) and delivery in group therapy format (12), probably the most notable advance with respect to the dissemination of CBT-I has been the development of webbased versions. To that end, there are now several versions of online CBT-I available across the globe.…”
mentioning
confidence: 99%